Discretion in Street-Level Bureaucracy, Public Service Responsiveness, and Service Justice in Indonesia: A Systematic Literature Review - Julianis; Entang Adhy Muhtar; Nina Karlina (Journal of Educational Studies, 2026)
Public service is one of the core functions of government that directly influences public trust in the state. In the implementation of public policies, frontline government officials or street-level bureaucrats play a crucial role in translating policies into services experienced by citizens. One important aspect of street-level bureaucracy is bureaucratic discretion, which allows public officials to adjust policy implementation to the needs of society. This study aims to analyze the relationship between discretion in street-level bureaucracy, public service responsiveness, and service equity in Indonesia. This research employs a Systematic Literature Review (SLR) approach following the PRISMA guidelines. The data were obtained from scholarly articles indexed in several academic databases, including Google Scholar, Scopus, Semantic Scholar, and Dimensions. The literature selection process resulted in 20 articles that were further analyzed through bibliometric analysis using VOSviewer and thematic analysis. The findings indicate that bureaucratic discretion plays an important role in improving public service responsiveness by enabling frontline bureaucrats to adjust services to the needs of citizens. However, the use of discretion also has the potential to create service inequities if it is not accompanied by adequate supervision and accountability mechanisms. Therefore, strengthening the capacity of frontline bureaucrats and developing transparent and accountable public service systems are essential to ensure that public services are delivered responsively while maintaining the principles of service equity.